(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Due to the important role played by public oil companies in Iraq in the development of the oil and gas sector and the achievement of revenues on which the state budget depends, they strive to diversify the contracts they conclude with specialized foreign companies to develop their performance and have recently tended to conclude partnership contracts with foreign companies to develop and improve their performance depending on the financial or human resources of these companies. Defining the concept of these contracts and explaining their legal adaptation and their role in supporting public companies is one of the important issues that should be identified for the purpose of providing a sound legal environment that enables companies to conclude these contracts and achieve the intended goals of them, and this is one of the main reasons that prompted us to research the concept of participation contracts.